Factors associated with knowledge, beliefs, and practices related to perinatal depression screening among rural maternal and child health workers: a multi-center cross-sectional study - Hongjuan Wang; Fan Xu; Rongzhi Li; Ting Pan; Siyuan Tang; Mei Sun (BMC Pregnancy and Childbirth)
Abstract Background Perinatal depression (PND) has been recognized as a public health problem worldwide. Maternal and Child Health (MCH) workers play a primary role in the initial risk reduction of PND by conducting screenings, identifying risk factors, providing support or crisis intervention, and referring for treatment. However, most rural MCH workers lack the necessary knowledge, beliefs, and practices related to PND screening. Aims To determine the levels of knowledge, beliefs, and practices regarding PND screening among rural MCH workers and identify associated factors. Methods A cross-sectional, multi-center study was conducted among 394 rural MCH workers (86.98% response rate) from 115 townships in Hunan province, China. Three self-administered questionnaires were developed to measure knowledge, beliefs and practices level related to PND screening. The data were analyzed using descriptive statistics, the Mann-Whitney U test, the Kruskal-Wallis H test, and binary logistic regression. Results The Cronbach’s α coefficient for the self-developed questionnaires ranged from 0.627 to 0.835. Over half of the MCH workers scored above the median levels in knowledge (56.1%), beliefs (70.1%) and practices (65.7%) related to PND screening. The amount of training on PND received was associated with levels of knowledge, beliefs, and practices regarding PND screening. Beliefs toward PND screening were also related to professional titles. Additionally, factors such as training received, type of institution, income, and gender were found to be associated with practices level. Conclusion Over half of the rural MCH workers obtained over median levels of knowledge, beliefs and screening practices related to PND. To improve these competencies, targeted annual training, increased income, reduced workload, and practical experience are recommended. Furthermore, developing reliable and valid assessment tools and conducting larger-scale surveys among rural MCH workers are essential. Clinical trial number Not applicable.